The coloring of batik stamp using songgolangit (Tridax procumbens) weeds with different fixation. Issue 1 (March 2021) - Dwicahya, K N; Musdalifah, M; Nurmasitah, S
Abstract: Natural dyes are from parts of plant, such as leaves, fruit, flowers, seeds, roots and bark. Weed is one of the plants that can be used as natural dyes. This study aims to determine the potential of Songgolangit weeds as natural dyes on batik stamp. This research is an experimental research. The objects of this study are Songgolangit weeds, batik stamp and the fixation (tunjung, alum, and quicklime). The data was collected by looking at the catalog of textile dyes to find out the direction of the resulting color. The sharpness of the motif was tested by using organoleptic tests. The result of the color direction analysis of alum fixation is Hazelwood. The quicklime fixation result is Bone and the tunjung fixation result is Hazelnut. The sharpest motif is produced from tunjung fixation. In conclusion, Songgolangit weeds can be used as natural dyes of batik stamp. The direction of the color produced differs depending on the fixation substance used.